Answer:
- 6
Step-by-step explanation:
The average rate of change of f(x) in the closed interval [ a, b ] is
![\frac{f(b)-f(a)}{b-a}](https://tex.z-dn.net/?f=%5Cfrac%7Bf%28b%29-f%28a%29%7D%7Bb-a%7D)
Here [ a, b ] = [ - 1, 4 ] , then
f(b) = f(4) = 4³ - 6(4)² - 4 = 64 - 96 - 4 = - 36
f(a) = f(- 1) = (- 1)³ - 6(- 1)² - (- 1) = - 1 - 6 + 1 = - 6 , then
average rate of change =
=
=
= - 6
(3x²y⁶)⁷
(3x²y⁶)(3x²y⁶)(3x²y⁶)(3x²y⁶)(3x²y⁶)(3x²y⁶)(3x²y⁶)
2187x¹⁴y⁴²
Answer:440.925
Step-by-step explanation:
Answer:
y=2-5x/4 x=8/5-4y/5
Step-by-step explanation: